Residents' assessment of local government road infrastructure delivery in Ile-Ife, Nigeria. (June 2019) - Olojede, Olorunfemi A; Agbola, Samuel B; Samuel, Kayode J
Ensuring adequate provision of municipal infrastructure, utilities and services constitutes a major rationale for the local government administration in Nigeria. This paper examined the road infrastructure delivery performance (provision, maintenance and rehabilitation) of the local administration in the two local government areas of Ile-Ife, Nigeria. Data were obtained with the aid of questionnaire and key-informant interview. Using multistage sampling, 600 residents were surveyed. The key-informant interviews were conducted on three local government senior administrative officers. Descriptive statistics and thematic content analysis were employed in the analysis. The study found that the local administrations in the city lacked autonomy, as they practically advance the cause of the state government. Thus, they could neither initiate nor execute any infrastructure project independently. It was also found that residents in the city were often required to contribute financially towards the construction and maintenance of transport infrastructure in their neighbourhoods. The study concluded that the performance of the local administration in the city was poor in terms of its statutory duty of municipal road infrastructure delivery. Consequently, the paper recommends the enhancement of the overall performance of local administration in Osun State through the granting of full political and financial autonomy to the local government.